Decoding the trajectory of antibiotic resistance genes in saline and alkaline soils: Insights from different fertilization regimes - Dandan Zhang; Jie Li; Guilong Zhang; Yan Xu (Environment International)
The soil salinity and alkalinity play an important role in the occurrence and proliferation of antibiotic resistance genes (ARGs). Yet, little is known the underlying mechanism by which soil salinity and alkalinity affect antibiotic resistance evolution. Here we investigated the ARGs variation in soil salinity and alkalinity environments created by different fertilization, and explored the biological mechanisms that salinity and alkalinity alter the evolutionary paradigm of antibiotic resistance. The results showed the soil treated by organic fertilizer exhibited a low salinity, neutral level (TSD 239.20 μS/cm, pH 7.17). The ARG abundance in the OF treatment was the highest, keeping an average of 67.83 TPM. Beside the effect of direct input of organic fertilizer at the beginning, it was important to note that, ARGs abundance during planting showed significant correlations with pH and electric conductivity. We observed that changes in microbial survival strategies under different salinity and alkalinity conditions further affected ARG hosts abundance. Indoor experiments demonstrated that there was a survival trade-off between the growth of resistant bacteria and the evolution of antibiotic resistance in salinity and alkalinity environments. Meta-genomic and Meta-transcriptomic analysis consistently demonstrated bacterial antibiotic resistance was primarily associated with pyruvate, energy and lipid metabolic pathways. The functional gene related to salinity and alkalinity, like cysH, cysK, plsB and plsC showed negative correlations with MDR. Prokaryotic transcription assays validated these relations. This study well explains the prevalence of soil ARGs after different fertilization regimes and will give a deeper understanding for the effect of soil salinity and alkalinity on antibiotic resistance evolution.